Bacteriophage Cocktail and Microcin-Producing Probiotic Escherichia coli Protect Mice Against Gut Colonization With Multidrug-Resistant Escherichia coli Sequence Type 131 - Porter, Stephen B.; Johnston, Brian D.; Kisiela, Dagmara; Clabots, Connie; Sokurenko, Evgeni V.; Johnson, James R. (Frontiers in Microbiology, 2022)
Non-antibiotic measures are needed reduce the rate of infections due to multidrug-resistant organisms (MDROs), including by eliminating the commensal reservoir that underlies such strains' dissemination and leads to recurrent infections. Here, we tested a cocktail of pre-selected bacteriophages and an engineered microcin C7-producing probiotic Escherichia coli Nissle-1917 strain for their ability to reduce gut colonization by an E. coli strain from sequence type 131 (ST131)-H30R, which is the major clonal group of MDROs among extraintestinal clinical E. coli isolates. Although the bacteriophage cocktail was highly effective against ST131-H30R strains both in vitro and in a murine model of subcutaneous sepsis, it was only weakly and transiently effective against gut colonization by the target ST131-H30R strain (0.5 log10 decrease on d+1: P > 0.001; no significant effect on d+4 and beyond). The probiotic strain, while also highly active against ST131-H30R in vitro, was ineffective against ST131-H30R gut colonization despite its abundant presence in feces. Nonetheless, despite failing as decolonizing agents when administered separately, when co-administered the bacteriophage cocktail and probiotic strain exhibited striking synergy against ST131-H30R gut colonization. This combinatory effect was most pronounced on d+1 (3.3 log10 target strain decrease: P < 0.001), and persisted until d+7 (0.5 log10 decrease; P < 0.02.). Although by d+10 the ST131-H30R load was fully restored, these findings provide proof of concept for combined bacteriophage-plus-probiotic administration to reduce or, possibly, to prevent gut colonization with MDROs in high-risk individuals.